The effect of peer observation on consumption choices: evidence from a lab-in-field experiment - Antonia Grohmann; Sahra Sakha (Applied Economics, 2019)
We investigate the impact of peer observation on consumption decisions using a lab-in-field experiment. Respondents make consumption decisions either alone or under peer observation. We find evidence for peer effects. We are able to study these further by looking into the mechanism and performing detailed heterogeneity analysis. Concerning the mechanisms, we find evidence for an information channel. Further, we show that the consumption choice is influenced by how many people made the same decision previously, but not by who those people are, hence finding evidence of a psychological channel. Respondents with higher cognitive ability are less susceptible to peer effects, while people living in small villages are more susceptible.
Keywords: D12; C93; O12; 330; Consumption; Peer effects; Conformity